A Pest Management Model with Stage Structure and Impulsive State Feedback Control. (3rd August 2015) - Pang, Guoping; Liang, Zhiqing; Xu, Weijian; Li, Lijie; Fu, Gang
Abstract : A pest management model with stage structure and impulsive state feedback control is investigated. We get the sufficient condition for the existence of the order-1 periodic solution by differential equation geometry theory and successor function. Further, we obtain a new judgement method for the stability of the order-1 periodic solution of the semicontinuous systems by referencing the stability analysis for limit cycles of continuous systems, which is different from the previous method of analog of Poincarè criterion. Finally, we analyze numerically the theoretical results obtained.